2022
DOI: 10.1177/23259671221091252
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Suture Tape Internal Brace Reinforcement of Soft Tissue Allografts for ACL Reconstruction Using a Porcine Model

Abstract: Background: Internal bracing of anterior cruciate ligament (ACL) surgery is a newer concept gaining popularity. Purpose/Hypothesis: To assess the biomechanical performance of soft tissue ACL reconstruction allografts reinforced with suture tape. It was hypothesized that load to failure would increase and cyclic displacement would decrease at time zero in the constructs reinforced with internal brace suture tape compared with those without suture tape augmentation. Study Design: Controlled laboratory study. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Laboratory studies have shown the suture tape–augmented graft construct to be biomechanically stronger. 5-7,32,35,47,53 Bachmaier et al 7 showed significantly reduced elongation and higher ultimate failure load without stress shielding the hamstring graft. Wicks et al 53 demonstrated a 33% decrease in cyclic displacement and a 25% increase in yield strength with suture tape reinforcement without increasing graft construct stiffness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory studies have shown the suture tape–augmented graft construct to be biomechanically stronger. 5-7,32,35,47,53 Bachmaier et al 7 showed significantly reduced elongation and higher ultimate failure load without stress shielding the hamstring graft. Wicks et al 53 demonstrated a 33% decrease in cyclic displacement and a 25% increase in yield strength with suture tape reinforcement without increasing graft construct stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical studies have shown that adding suture tape reinforcement to a reconstruction significantly increases the ultimate tensile strength of the construct without stress shielding and reduces graft elongation. 6,7,29,53 This added strength may reduce ACL failure rates, particularly when the graft is most vulnerable. In addition, the greatest biomechanical effect has been demonstrated with small-diameter grafts.…”
mentioning
confidence: 99%
“…The posterior transeptal portal approach allows good visualization of the tibial tunnel preparation and protects the vital neurovascular structures 5 Allograft bone plugs facilitate revision in the onestage procedure 11 Internal brace augmentation protects the graft during the revascularization and remodeling process 12 Backup fixation is essential due to compromised bone stock in revision surgeries 4 Here are our references. Thank you for watching this video.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“… 11 , 12 The addition of suture or tape to serve as an augment for the ACL graft is easy to perform and does not necessitate a separate open incision. Further, this technique has demonstrated potential in improving both biomechanical 13 and clinical outcomes following ACL reconstruction. 14 Tape augmentation increases the strength of the graft complex, demonstrating greater load to failure and reduced elongation.…”
Section: Introductionmentioning
confidence: 99%